Analysis of Strategies to Improve the Effectiveness and Productivity of Promotions in Supporting Service Quality at Cordela Suite Hotel Tasikmalaya - Brata, Moh. Abdul Azis Danu; Sugiarti, Indah; Nurhapipah, Tridesmita; Fitran, Muhammad (Business Management Research, 2026)
This study examines the integrative relationship between promotional strategies and service quality within the hospitality industry by emphasizing the role of expectation formation and service delivery alignment. Drawing on Integrated Marketing Communication (IMC), Service-Dominant Logic (SDL), and expectation-disconfirmation theory, the study proposes a process-based framework linking promotion, customer expectations, and perceived service quality. A qualitative case study was conducted at Cordela Suite Hotel Tasikmalaya, a regional hotel operating in a competitive and under-researched context. Data were collected through semi-structured interviews, observations, and document analysis, and analyzed using thematic coding (open, axial, and selective coding). The findings reveal that promotional strategies function as expectation builders, shaping customer perceptions prior to service encounters. Promotional effectiveness influences perceived service quality by determining the accuracy of communicated value, while promotional productivity affects the consistency of service delivery through operational readiness. Importantly, alignment between promotional promises and actual service delivery emerges as a critical mechanism driving customer satisfaction and loyalty. This study contributes to the literature by offering an integrative and process-oriented perspective that bridges marketing and service operations, moving beyond fragmented approaches that treat promotion and service quality separately. Practically, the findings provide actionable insights for hotel managers, particularly in regional contexts, to synchronize promotional activities with operational capabilities in order to enhance customer experience and competitive performance.